Chapter 5 'Make Scandinavia a bulwark against fascism!' Hitler's seizure of power and the transnational anti-fascist movement in the Nordic countries - Braskén, Kasper (Taylor & Francis, 2021)
Hitler's seizure of power on 30 January 1933 provided an urgent impetus to stage transnational anti-fascist conferences and rallies on a global scale. One of the first, but almost completely overlooked major conferences was organised in Copenhagen in April 1933 in the form of a Scandinavian Anti-Fascist Conference. The chapter will use the event as a prism to look backwards at anti-fascist activism in the Nordic countries during the preceding years and follow its transformation process in its immediate aftermath. What form did these largely overlooked anti-fascist articulations and manifestations take, and how were they connected to the rising transnational and global anti-fascist mobilisation coordinated in Paris and London? The chapter shows that the establishment of the Third Reich, on the one hand, vitalised anti-fascism in Scandinavia but that it paradoxically, on the other, further sharpened the communist critique of reformist social democracy and empowered social democratic anti-communism. Moreover, small neutral states, especially with social democratic governments, were confronted with an acute dilemma as the German foreign office made it clear that sharp critique of Nazi Germany and Hitler in the Nordic press and social movements had to be limited in order to maintain good bilateral relations.